2016
DOI: 10.1177/0265407516669604
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit communal coping in couples with recently diagnosed type 2 diabetes

Abstract: When an individual in a close relationship is diagnosed with a chronic illness, coping can be the responsibility of the patient, or couple-members can cope communally. Communal coping reflects a shared appraisal of a stressor (our problem instead of my problem) and collaborative efforts to address the stressor. The current study examined whether patients’ and partners’ communal coping levels were associated with relational and health functioning among 70 couples in which one member was recently diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
90
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 57 publications
10
90
2
Order By: Relevance
“…However, the contextual risk factor of stigma is not experienced by couples affected by chronic diseases such as cancer and heart diseases, highlighting the unique nature of HIV research. In line with previous studies that were dominantly conducted in Western cultures (Badr et al, 2016; Helgeson et al, 2017;Zajdel et al, 2018), our findings in Chinese HIV serodiscordant couples also demonstrate the protective role of couple identity. Moreover, the present study provides quantitative and longitudinal support for the long-existing clinical strategy of fostering couple identity to improve couple adjustment (Heinrichs et al, 2012;Montgomery et al, 2012;Reid, Dalton, Laderoute, Doell, & Nguyen, 2006) in the HIV context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the contextual risk factor of stigma is not experienced by couples affected by chronic diseases such as cancer and heart diseases, highlighting the unique nature of HIV research. In line with previous studies that were dominantly conducted in Western cultures (Badr et al, 2016; Helgeson et al, 2017;Zajdel et al, 2018), our findings in Chinese HIV serodiscordant couples also demonstrate the protective role of couple identity. Moreover, the present study provides quantitative and longitudinal support for the long-existing clinical strategy of fostering couple identity to improve couple adjustment (Heinrichs et al, 2012;Montgomery et al, 2012;Reid, Dalton, Laderoute, Doell, & Nguyen, 2006) in the HIV context.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Pomeroy and colleagues (2002) found that an intervention entailing the component of we-oriented coping with HIV improved the mental health of American heterosexual HIV serodiscordant couples. Our findings on the benefits of couple identity are also consistent with evidence in discordant couples living with other chronic diseases such as diabetes and cancer in other cultures that weness improved couple adjustment to illnesses (Badr et al, 2016;Helgeson, Jakubiak, Seltman, Hausmann, & Korytkowski, 2017;Zajdel et al, 2018). However, the contextual risk factor of stigma is not experienced by couples affected by chronic diseases such as cancer and heart diseases, highlighting the unique nature of HIV research.…”
Section: Discussionsupporting
confidence: 85%
“…However, evidence from this study suggests that cultural values for BA/BC men to take responsibility for themselves and others may explain their preference for a solo approach to manage their CaP challenges without “sharing the burden” or appearing vulnerable. Seminal literature on coping identified this behaviour as “protective buffering,” which has been associated with elevated psychosocial distress among people living with chronic illnesses and their caregivers . Adopting active engagement through open communications and shared problem solving with partners could help men deal with the psychological distress associated with feelings of lessened masculinity and also improve spousal adjustment to sexual dysfunction after CaP treatment …”
Section: Discussionmentioning
confidence: 99%
“…Seminal literature on coping 30 identified this behaviour as "protective buffering," which has been associated with elevated psychosocial distress among people living with chronic illnesses and their caregivers. 31,32 Adopting active engagement 30 through open communications and shared problem solving with partners could help men deal with the psychological distress associated with feelings of lessened masculinity 33 and also improve spousal adjustment to sexual dysfunction after CaP treatment. 34 The reference of men in this study to "fatherhood" as a coping strategy also demonstrates their resilient determination to move on with life regardless of the perceived cultural implications of losing their sexual virility (effeminate…”
Section: Category Supporting Quotesmentioning
confidence: 99%
“…In addition, a focus group of 30 couples revealed that couples who felt they were “in this together” were better able to communicate and support each other and were more likely to engage in diabetes self-management behaviors ( 23 ). Helgeson et al ( 33 ) found that implicit communal coping, as measured by first-person plural pronoun usage during a diabetes discussion, related to a reduction in patient distress and improved diabetes self-care behaviors. Although these findings suggest a relationship between partner investment and health behaviors, more research is needed to examine the extent to which this process is mediated by self-efficacy ( 34 ).…”
mentioning
confidence: 99%